Public health impact of foodborne exposure to naturally occurring virulence-attenuated Listeria monocytogenes: inference from mouse and mathematical models. Issue 1 (13th December 2019) - Stout, Alison; Van Stelten-Carlson, Anna; Marquis, Hélène; Ballou, Michael; Reilly, Brian; Loneragan, Guy H.; Nightingale, Kendra; Ivanek, Renata
Abstract : Listeriosis is a clinically severe foodborne disease caused by Listeria monocytogenes (Lm). However, approximately 45% of Lm isolates in food carry a virulence-attenuating single-nucleotide polymorphism in inlA, which normally facilitates crossing the intestinal barrier during the initial stages of infection. We hypothesized that (i) natural exposure to virulence-attenuated (vA) Lm strains through food can confer protective immunity against listeriosis attributable to fully virulent (fV) strains and (ii) current food safety measures to minimize exposure to both Lm strains may have adverse population-level outcomes. To test these hypotheses, we evaluated the host response to Lm in a mouse infection model and through mathematical modelling in a human population. After oral immunization with a murinized vA Lm strain, we demonstrated the elicitation of a CD8+ T-cell response and protection against subsequent challenge with an fV strain. A two-strain compartmental mathematical model of human exposure to Lm with cross-protective immunity was also developed. If food safety testing strategies preferentially identify and remove food contaminated by vA strains (potentially due to their common occurrence in foods and higher concentration in food compared to fV strains), the model predicted minimal public health benefit to potentially adverse effects. For example, reducing vA exposures by half, while maintaining fV exposures results in an approximately 6% rise in annual incidence.